Suppressor of cytokine signaling 2 (Socs2) deletion protects bone health of mice with DSS-induced inflammatory bowel disease - Ross Dobie; Vicky E. MacRae; Chloe Pass; Elspeth M. Milne; S. Faisal Ahmed; Colin Farquharson (The Company of Biologists, 2018)
Individuals with inflammatory bowel disease (IBD) often present with poor bone health. The development of targeted therapies for this bone loss requires a fuller understanding of the underlying cellular mechanisms. Although bone loss in IBD is multifactorial, the altered sensitivity and secretion of growth hormone (GH) and insulin-like growth factor-1 (IGF-1) in IBD is understood to be a critical contributing mechanism. The expression of suppressor of cytokine signaling 2 (SOCS2), a well-established negative regulator of GH signaling, is stimulated by proinflammatory cytokines. Therefore, it is likely that SOCS2 expression represents a critical mediator through which proinflammatory cytokines inhibit GH/IGF-1 signaling and decrease bone quality in IBD. Using the dextran sodium sulfate (DSS) model of colitis, we reveal that endogenously elevated GH function in the Socs2−/− mouse protects the skeleton from osteopenia. Micro-computed tomography assessment of DSS-treated wild-type (WT) mice revealed a worsened trabecular architecture compared to control mice. Specifically, DSS-treated WT mice had significantly decreased bone volume, trabecular thickness and trabecular number, and a resulting increase in trabecular separation. In comparison, the trabecular bone of Socs2-deficient mice was partially protected from the adverse effects of DSS. The reduction in a number of parameters, including bone volume, was less, and no changes were observed in trabecular thickness or separation. This protected phenotype was unlikely to be a consequence of improved mucosal health in the DSS-treated Socs2−/− mice but rather a result of unregulated GH signaling directly on bone. These studies indicate that the absence of SOCS2 is protective against bone loss typical of IBD. This study also provides an improved understanding of the relative effects of GH/IGF-1 signaling on bone health in experimental colitis, information that is essential before these drugs are explored as bone protective agents in children and adults with IBD.